Modulating Androgen Receptor-Driven Transcription in Prostate Cancer with Selective CDK9 Inhibitors. Issue 2 (18th February 2021) - Richters, André; Doyle, Shelby K.; Freeman, David B.; Lee, Christina; Leifer, Becky S.; Jagannathan, Sajjeev; Kabinger, Florian; Koren, Jošt Vrabič; Struntz, Nicholas B.; Urgiles, Julie; Stagg, Ryan A.; Curtin, Brice H.; et al.
Summary: Castration-resistant prostate cancers (CRPCs) lose sensitivity to androgen-deprivation therapies but frequently remain dependent on oncogenic transcription driven by the androgen receptor (AR) and its splice variants. To discover modulators of AR-variant activity, we used a lysate-based small-molecule microarray assay and identified KI-ARv-03 as an AR-variant complex binder that reduces AR-driven transcription and proliferation in prostate cancer cells. We deduced KI-ARv-03 to be a potent, selective inhibitor of CDK9, an important cofactor for AR, MYC, and other oncogenic transcription factors. Further optimization resulted in KB-0742, an orally bioavailable, selective CDK9 inhibitor with potent anti-tumor activity in CRPC models. In 22Rv1 cells, KB-0742 rapidly downregulates nascent transcription, preferentially depleting short half-life transcripts and AR-driven oncogenic programs. In vivo, oral administration of KB-0742 significantly reduced tumor growth in CRPC, supporting CDK9 inhibition as a promising therapeutic strategy to target AR dependence in CRPC. Graphical Abstract: Highlights: KI-ARv-03 reduces AR protein levels and AR-driven transcription KI-ARv-03 is deduced to be a potent, ultraselective inhibitor of CDK9 Optimization led to the orally bioavailable and selective CDK9 inhibitor KB-0742 KB-0742 displays potent anti-tumor activity in cancer models in vitro and in vivo Abstract : In the pursuit of hormone receptor modulators in prostate cancer, a potent, ultraselective CDK9 inhibitor is discovered. This study describes the most selective inhibitors of CDK9 known to date and provides compelling preclinical in vitro and in vivo support for CDK9 as a therapeutic target.